The Predator and his Prey: Strategies and Strangenesses in Beckett's Early Poems. Issue 1 (April 2015) - Pilling, John
<x xml:space="preserve">Abstract</x> A study of the difficulties encountered in selected early poems of Samuel Beckett (specifically, 'Casket of Pralinen …' and 'Text'), investigating the adequacy of 'the probity with which the creative act has carried itself out', together with a more general consideration of the psychological pressures which Beckett's creativity was being called on to meet.